2020
DOI: 10.1155/2020/9762390
|View full text |Cite
|
Sign up to set email alerts
|

DpdtC-Induced EMT Inhibition in MGC-803 Cells Was Partly through Ferritinophagy-Mediated ROS/p53 Pathway

Abstract: Epithelial-mesenchymal transition (EMT) is a cellular process in which epithelial cells are partially transformed into stromal cells, which endows the polarized epithelium cells more invasive feature and contributes cancer metastasis and drug resistance. Ferritinophagy is an event of ferritin degradation in lysosomes, which contributes Fenton-mediated ROS production. In addition, some studies have shown that ROS participates in EMT process, but the effect of ROS stemmed from ferritin degradation on EMT has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 56 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…Caryophyllene oxide also influenced their cell morphology, affected their cell migration, and increased cell apoptosis and death. According to the findings of several studies ( Hou et al, 2016 ; Feng et al, 2020 ; Fuhrmann et al, 2020 ; Yang et al, 2021 ), the occurrence of ferroptosis is closely related to oxidative stress. Ferroptosis is characterized by the buildup of lipid peroxidation to deadly levels.…”
Section: Discussionmentioning
confidence: 99%
“…Caryophyllene oxide also influenced their cell morphology, affected their cell migration, and increased cell apoptosis and death. According to the findings of several studies ( Hou et al, 2016 ; Feng et al, 2020 ; Fuhrmann et al, 2020 ; Yang et al, 2021 ), the occurrence of ferroptosis is closely related to oxidative stress. Ferroptosis is characterized by the buildup of lipid peroxidation to deadly levels.…”
Section: Discussionmentioning
confidence: 99%
“…After iron enters the circulation, it is oxidized by hephaestin or ceruloplasmin to Fe 3+ , which binds to transferrin. Additionally, ferritin can be transported by the Prominin-2 polyvesicle–exosome pathway out of the cell when the cell is overloaded with iron ( Gao et al, 2016 ; Zhou et al, 2018 ; Feng H et al, 2020 ); and 3) iron storage—Fe 2+ enters the cells to form cytoplasmic labile iron pool (LIP) ( Kakhlon and Cabantchik, 2002 ; Feng J et al, 2020 ). One part of Fe 2+ is stored as ferritin, and the other part is used for various biochemical processes.…”
Section: Regulatory Mechanism Of Ferritinophagymentioning
confidence: 99%
“…DSF and DTCs, in combination with metal ions, can induce ROS production through the Fenton and Haber Weiss reaction, and also by inhibiting antioxidants such as superoxide dismutase and glutathione ( Marikovsky et al., 2002 ; Skrott and Cvek, 2012 ). A recent article showed that a dipyridylhydrazone DTC induced ferritinophagy by mobilizing iron from ferritin and mediating the ROS/p53 pathway, resulting in the inhibition of gastric cancer cell line proliferation ( Feng et al., 2020 ; Huang et al., 2018 ).…”
Section: Dithiocarbamates: New Allies In the Fight Against Cancermentioning
confidence: 99%